Jpop: Fenomena Englishization dalam Lirik Lagu Berbahasa Jepang - Gede Satya Hermawan (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2013)
This article discusses about Jpop (Japanese Popular Music). It explores englishization in JPop(Japanese Popular Music) in the light of recent theoretical development of sociocultural linguistic.This article also shows of englishization can refashions diction in a song lyrics, and draws attention tothe way that sociocultural becames a force to provoke such refashioning.